Gender roles in an agrarian community : a case study of longhouse workforce in the Kanowit district - Roger Juing, anak Gabriel Adit (Faculty of Social Sciences, 2004)
The effects of cash on the social structure of the rural communities as a result of the monetary economy are still very much unknown. This study attemps to determine the degree of labour diversification among longhouse communities in Kanowit. The specific objectives are to determine gender roles in farming and non-farming activities and the extent of labour exchange practice or 'beduruk' among longhouse communities, to assess the participation of women in the informal sector (selling farm and jungle produce; handicraft, baby-sitting, street-vending, housekeeping) and to determine the effect of wage labor on social relations among longhouse communities in Kanowit.